RELATIONSHIP OF AWARDS IN MULTIPLE CHOICE QUESTIONS AND STRUCTURED ANSWER QUESTIONS IN THE UNDERGRADUATE YEARS AND THEIR EFFECTIVENESS IN EVALUATION - Khan, Junaid Sarfraz; Mukhtar, Osama; Tabasum, Saima; Shaheen, Naveed; Farooq, M.; Irfan, M. Abdul; Sattar, Ajmal; Nabeel, M.; Imran, M.; Rafique, Sadia; Iqbal, Maryam; Afzal, M. Sheraz; et al. (Journal of Ayub Medical College Abbottabad, 2010)
Background: A number of evaluation tools for assessing the cognitive and affective domains in accordance with Bloom's taxonomy are available for summative assessment. At the University of Health Sciences, Lahore, Multiple Choice Questions (MCQs) and Structured Answer Questions (SAQs) are used for the evaluation of the cognitive domain at all six hierarch levels of taxonomy using the tables of specifications to ensure content validity. The rationale of having two evaluation tools seemingly similar in their evaluative competency yet differing in feasibility of construction, administration and marking is being challenged in this study. Methods: The MCQ and SAQ awards of the ten percent sample population amounting to 985 students in fifteen Medical and Dental Colleges across Punjab were entered into SPSS-15 and correlated according to the cognitive and affective level of assessment in relation to the Bloom's taxonomy and their grouping in the Tables of Specifications, using parametric tests. 3494 anonymously administered questionnaires were analyzed using ethnograph. Results: No statistically significant difference was found in the mean marks obtained by the students when MCQs and SAQs were compared according to their groupings in the Tables of Specifications at all levels of cognitive hierarchical testing. End-of-year cognitive level testing targets set were not met and more questions were set at the lower cognitive testing levels. Expenses incurred in setting MCQs and SAQs were comparable but conduct and assessment costs for MCQs and SAQs were 6% and 94% of the total respectively. In both MCQs and SAQs students performed better at higher cognitive testing levels whereas the SAQs and MCQs were able to marginally test the lower levels of affective domain only. Student's feedback showed that attempting MCQs required critical thinking, experience and practice. Conclusion: MCQs are more cost effective means at levels of cognitive domain assessment. Keywords: Cognitive Domain, Affective Domain, Bloom's Taxonomy, Tables of Specifications, Evaluation